O-20 Using project ECHO™ to deliver palliative care education and support across multiple settings. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Diffin, Janet; McTernaghan, Tracey; McMullan, Aine; Hayes, Martin; Watson, Max
Abstract : Background: There is a need for high quality palliative care education and support, but often limited resources are available. Project ECHO™ (Extension for Community Healthcare Outcomes) is a tele-mentoring programme which could overcome this gap by using video-conferencing technology to deliver: Evidence–based, best practice guidance and education from specialists; Case–based learning with opportunities for questions and discussion with peers. Five ECHO™ networks in Northern Ireland (NI) delivered palliative care education and support: Cardiology/heart failure; District nurses; Palliative care pharmacy; Paediatric palliative care; Marie Curie registered nurses. Network participants identified educational topics for their curriculum, and set network aims and objectives. Objectives included increasing participants' knowledge, skills and confidence in palliative care related areas, improving collaboration, and facilitating peer support. Network leads were responsible for evaluating how well objectives were met. Aim: To evaluate how successful each ECHO™ network was in achieving it aims and objectives. Methods: Retrospective online survey designed specifically for each network issued to registered participants after the final ECHO™ session. Results: Across the five networks, 45 ECHO™ sessions were delivered with 194 participants attending at least two. 27% (60/224) registered participants across each network responded to the survey. Overall, each network was successful in achieving its aims. The majority of participants reported increased knowledge and confidence in relation to the areas assessed. ECHO™ was identified as a suitable model for delivering education and the opportunity for case-based learning was valued. Direct impacts on practice included improved inter-agency working and networking, improved communication with patients and families, and improved confidence to manage similar cases in the future. Barriers to participation included time restraints due to staffing issues or workload. Conclusion: Project ECHO™ may be an ideal methodology for delivering palliative care education and support to a range of practitioners. However, protected time for participation is recommended. Funders: Health and Social Care Board NI/Hospice UK.